ARTERIAL HYPERTENSION IN THYROTOXICOSIS AND REMODELING OF THE LEFT VENTRICLE OF THE HEART - Khusainova Munira Alisherovna; Salimova Dildora Erkinovna; Boykobilov Sukhrob Duskobilovich; Turdiyev Husan Samandarovich (Ta'lim innovatsiyasi va integratsiyasi, 2024)
The purpose of the study. The article presents the results of assessing the incidence of arterial hypertension (AH) in thyrotoxicosis (T), its nature, its effect on the nature of left ventricular remodeling (LV) and the prognosis of cardiovascular complications. Results and conclusions. The data obtained demonstrated that hypertension develops with a high frequency and is predominantly systolic in nature. In patients with normal blood pressure, LV hypertrophy (LVH) was exceptionally eccentric. The development of hypertension was accompanied by an increase in the frequency of LVH, mainly due to its concentric version. Concentric LVH, in turn, was associated with the highest incidence of atrial fibrillation and heart failure in the examined patients.